Аналіз методів планування шляху мобільного робота в групі - Печенов, М. А. (ХНУРЕ, 2024)
The most common way to define a path planning (motion planning) problem is that an agent needs to move from an initial position to a goal, avoiding obstacles and achieving cost minimization.
Keywords: шлях мобільного робота; планування шляху робота